Channel Estimation by Exploiting Sublayer Information in OFDM Systems - Bevermeier, Maik; Ebel, Tobias; Haeb-Umbach, Reinhold (Multi-Carrier Spread Spectrum 2007)

Combined Time and Frequency Domain OFDM Channel Estimation - Bevermeier, Maik; Haeb-Umbach, Reinhold (Multi-Carrier Spread Spectrum 2007)

OFDM Channel Estimation Based on Combined Estimation in Time and Frequency Domain - Haeb-Umbach, Reinhold; Bevermeier, Maik (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2007))
In this paper we present a novel channel impulse response estimation technique for block-oriented OFDM transmission based on combining estimators: the estimates provided by a Kalman filter operating in the time domain and a Wiener filter in the frequency domain are optimally combined by taking into account their estimated error covariances. The resulting estimator turns out to be identical to the MAP estimator of correlated jointly Gaussian mean vectors. Different variants of the proposed scheme are experimentally investigated in an EEEE 802.11a-like system setup. They compare favourably with known approaches from the literature resulting in reduced mean square estimation error and bit error rate. Further, robustness and complexity issues are discussed
Keywords: bit error rate; block-oriented OFDM transmission; channel estimation; channel impulse response estimation; combining estimators; error statistics; frequency domain estimation; Gaussian mean vectors; Gaussian processes; Kalman filter; Kalman filters; MAP estimator; maximum likelihood estimation; OFDM channel estimation; OFDM modulation; time domain estimation; time-frequency analysis; Wiener filter; Wiener filters

A Novel Similarity Measure for Positioning Cellular Phones by a Comparison With a Database of Signal Power Levels - Haeb-Umbach, Reinhold; Peschke, Sven (IEEE Transactions on Vehicular Technology)
In this paper, we propose a novel similarity measure to be used for localizing mobile terminals by comparing measured signal power levels with a database of predictions. The proposed measure provides the possibility to incorporate inherent information about signal power level measurements requested by the serving base station but not reported by the mobile terminal. Increased positioning accuracy was observed both in simulations and with real field data
Keywords: cellular phone positioning; cellular radio; measured signal power levels; mobile handsets; mobility management (mobile radio)

Multi-Resolution Soft Features for Channel-Robust Distributed Speech Recognition - Ion, Valentin; Haeb-Umbach, Reinhold (Interspeech 2007)

Velocity Estimation of Mobile Terminals by Exploiting GSM Downlink Signalling - Peschke, Sven; Haeb-Umbach, Reinhold (4th Workshop on Positioning Navigation and Communication (WPNC 2007))
In this paper, we experimentally evaluate algorithms for velocity estimation of a GSM 900 mobile terminal which are based on the analysis of the statistical properties of the fast fading process. It is shown how theses statistics can be obtained from the training sequences present in downlink transmission bursts without establishing an active connection. Realistic simulations of a GSM channel according to the COST 207 channel models have been conducted. These models incorporate effects like multipath propagation, fading, cochannel interference and additive noise. It is shown that velocity estimation by searching for the maximum slope of the power density spectrum of the fast fading performs best.
Keywords: additive noise; cellular radio; channel estimation; cochannel interference; COST 207 channel models; downlink transmission bursts; fading channels; fading process; GSM downlink signalling; mobile terminals; multipath channels; multipath propagation; power density spectrum; statistical analysis; statistical properties; telecommunication links; telecommunication terminals; velocity estimation

Blind Acoustic Beamforming Based on Generalized Eigenvalue Decomposition - Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
Maximizing the output signal-to-noise ratio (SNR) of a sensor array in the presence of spatially colored noise leads to a generalized eigenvalue problem. While this approach has extensively been employed in narrowband (antenna) array beamforming, it is typically not used for broadband (microphone) array beamforming due to the uncontrolled amount of speech distortion introduced by a narrowband SNR criterion. In this paper, we show how the distortion of the desired signal can be controlled by a single-channel post-filter, resulting in a performance comparable to the generalized minimum variance distortionless response beamformer, where arbitrary transfer functions relate the source and the microphones. Results are given both for directional and diffuse noise. A novel gradient ascent adaptation algorithm is presented, and its good convergence properties are experimentally revealed by comparison with alternatives from the literature. A key feature of the proposed beamformer is that it operates blindly, i.e., it neither requires knowledge about the array geometry nor an explicit estimation of the transfer functions from source to sensors or the direction-of-arrival.
Keywords: acoustic signal processing; arbitrary transfer function; array signal processing; blind acoustic beamforming; direction-of-arrival; direction-of-arrival estimation; eigenvalues and eigenfunctions; generalized eigenvalue decomposition; gradient ascent adaptation algorithm; microphone arrays; microphones; narrowband array beamforming; sensor array; single-channel post-filter; spatially colored noise; transfer functions

Blind Adaptive Principal Eigenvector Beamforming for Acoustical Source Separation - Warsitz, Ernst; Haeb-Umbach, Reinhold; Tran Vu, Dang Hai (Interspeech 2007)

An Approach to Iterative Speech Feature Enhancement and Recognition - Windmann, Stefan; Haeb-Umbach, Reinhold (Interspeech 2007)

The DYMO Routing Protocol in VANET Scenarios - Sommer, Christoph; Dressler, Falko (2007 IEEE 66th Vehicular Technology Conference)

Das Edirom-Projekt. Werkzeuge für digitale Formen wissenschaftlich-kritischer Musikeditionen - Kepper, Johannes; Röwenstrunk, Daniel (Forum Musikbibliothek)
Keywords: Edirom; ViFE

Liquid analysis using acoustical sensors - Henning, Bernd

Schallfeldsimulation für die Ultraschallmesstechnik - Henning, Bernd
Ultraschallsensoren werden heute in der industriellen Messtechnik vielfach eingesetzt, zum Beispiel für die Durchflussmessung, Füllstandmessung, Konzentrationsanalyse, zerstörungsfreie Werkstoffdiagnostik und anderes mehr. Dabei wachsen die Anforderungen hinsichtlich der zu gewährleistenden Messunsicherheit, der Zuverlässigkeit sowie einer erweiterter Funktionalität ständig. Erreichen lassen sich diese Ziele natürlich nur mit Hilfe verbesserter Ultraschallsensoren und optimal gestalteter Messanordnungen. Die permanente Forderung, die Produktentwicklungszeiten sowie die Produktherstellungskosten deutlich zu minimieren, macht den Einsatz moderner Entwicklungswerkzeuge für das Sensordesign unumgänglich.

Acoustical waveguides for sensor applications - Henning, Bernd; Rautenberg, Jens
The continuous measurement of rheological properties (density and viscosity) or material properties (concentration of selected substances) of liquid mixtures in the chemical industry or in the food industry is a great challenge to this day. Standard chemical sensors are often not suitable for industrial processes because of their slow sensor response and their limited robustness due to the direct contact to process media. Ultrasonic sensor systems meet the practical requirements of a chemical sensor quite well. Current ultrasonic sensor systems are already widely used as acoustic chemical sensors to measure concentration of selected substances or to monitor the course of polymerization, crystallization or fermentation processes. Useable acoustic properties for the characterization of liquid mixtures are sound velocity, sound absorption and acoustic impedance in consideration of temperature. This contribution will give a short overview of the state of the art and several trends for the use of ultrasonic sensor systems in process applications. Currently there are many activities to use acoustic waveguides for above mentioned sensor applications. By means of two selected examples (density measurement and determination of acoustic properties of highly absorbing synthetic polymers) it will presented new developed measurement principles using acoustic waveguides.

Measurement of the acoustic properties of highly absorbing synthetic polymers - Rautenberg, Jens; Henning, Bernd (Proceedings of the International Congress on Ultrasonics)
There are a couple of acoustic systems that are well suited for continuous and reliable concentration measurement of liquids, but the reliability is a great challenge: Most systems determine the amplitude ratio of deflected ultrasound bursts at different boundaries as well as the sound velocity of the liquid in order to calculate its acoustic impedance and therewith its density. The problem is the sensitivity of variations of reference material properties as well as abrasion or soiling of the boundaries. This contribution is about a new model-based method that uses the whole surface of an acoustic waveguide as reference boundary. On the one hand the integral over a large boundary decreases influence of small boundary defects. On the other hand it is possible to analyze different modes of sound in the fluid. This redundancy can be used to increase reliability. The decomposition of the received signal in its modal components by means of principle component analysis will be discussed in detail. It will be shown that it is possible to determine the amplitudes of each mode by means of one measured signal at the end of the waveguide, even if the transducer and the electronic components are of very simple kind

New approach for the reliable measurement of acoustic impedance of liquids in an acoustic waveguide - Rautenberg, Jens; Henning, Bernd
Continuous and reliable concentration measurement of liquids still is a great challenge as the sensor systems have to meet high industrial requirements. Apart from chemical sensors there are a couple of acoustic systems [1] that are well suited for a lot of industrial applications. Most of them determine the amplitude ratio of deflected ultrasound bursts at different boundaries as well as the sound velocity of the liquid in order to calculate its acoustic impedance and therewith its density. The advantages of acoustic sensors are their robustness and their fast response. Their disadvantages are sensitivity against variations of the reference material properties as well as abrasion or soiling of the boundaries. This contribution is about a new model-based method that uses the whole surface of an acoustic waveguide as reference boundary: It has turned out that the principal components of a signal at the end of the waveguide can be assigned to the different propagative acoustic modes (Fig. 1). Therefore it is necessary to use different simulation tools, e.g. FEM and modal analysis (Fig. 2). With this it is possible to determine the amplitudes of each mode by means of one measured signal at the end of the waveguide and Gauss Algorithm even if the transducer is of very simple kind [2]. Therewith it is possible to get redundant information -- one amplitude for each mode -- for the liquid impedance. In addition to that it is possible to generate an acoustic reference signal without information about the liquid impedance but dissipation if we use the fundamental mode. The different signal amplitudes and a model of acoustic wave propagation [2, 3] offer the possibility to distinguish between dissipation in the liquid and attenuation due to the impedance relations. Moreover, if there are enough analysable amplitudes available, variations of the reference material properties can be determined.

Separation of mode-specific signals in a fluid-filled circular waveguide - Rautenberg, Jens; Henning, Bernd (Proceedings of the International Congress on Ultrasonics)
There are a couple of acoustic systems that are well suited for continuous and reliable concentration measurement of liquids, but the reliability is a great challenge: Most systems determine the amplitude ratio of deflected ultrasound bursts at different boundaries as well as the sound velocity of the liquid in order to calculate its acoustic impedance and therewith its density. The problem is the sensitivity of variations of reference material properties as well as abrasion or soiling of the boundaries. This contribution is about a new model-based method that uses the whole surface of an acoustic waveguide as reference boundary. On the one hand the integral over a large boundary decreases influence of small boundary defects. On the other hand it is possible to analyze different modes of sound in the fluid. This redundancy can be used to increase reliability. The decomposition of the received signal in its modal components by means of principle component analysis will be discussed in detail. It will be shown that it is possible to determine the amplitudes of each mode by means of one measured signal at the end of the waveguide, even if the transducer and the electronic components are of very simple kind.

Ultraschallzähler - Sonnenberg, Hans-Michael; Schmidt-Schoenian, Axel; Rautenberg, Jens; Unverzagt, Carsten; Kehl, Romina; Henning, Bernd

Sensorelektronik zur Bestimmung von Reflexionen sensoroberflächennaher Schichten - Vössing, Torsten; Rautenberg, Jens; Henning, Bernd (Fortschritte der Akustik)
In der Ultraschallmesstechnik ist der Einsatz des Impuls-Echoverfahrens verbreitet. Wird nur ein Ultraschallwandler eingesetzt, benötigt man für das sequentielle Senden und Empfangen einen Sende-/Empfangsumschalter. Häufig werden aber nicht nur Impulse gesendet, sondern auch sogenannte Bursts, die aus mehreren Wellenzügen bestehen. Die während des Sendebetriebs empfangenen Ultraschallwellen, die z. B. durch Reflexionen von nahe gelegenen Hindernissen entstehen, können bei diesen umschaltenden Systemen nicht ausgewertet werden. In diesem Beitrag wird eine Sensor-Interface-Elektronik vorgestellt, die das gleichzeitige Senden und Empfangen von Ultraschallsignalen mit nur einem Ultraschallwandler erlaubt. Die dazu erforderliche Trennung von Sende- und Empfangssignal wird durch einen Richtkoppler ermöglicht, der mit vergleichsweise geringem technischem Aufwand aus Breitbandübertragern aufgebaut ist. Eine geeignete Dimensionierung für die verkoppelten Übertrager wurde durch die Analyse der zugehörigen Streumatrix dieses Aufbaus gefunden. Die Arbeitsweise sowie die Bedeutung der Anpassung der Tore des Richtkopplers wird anhand der Ankopplung verschiedener Medien an den Wandler erläutert. Die angekoppelte akustische Last beeinflusst dabei auch die elektrischen Eigenschaften des Sensors. Durch den Einsatz dieser Sensorelektronik wird es möglich, Reflexionen in unmittelbarer Nähe der Sensoroberfläche aufzunehmen, ohne dass z. B. Vorlaufkörper eingesetzt werden müssen. Möglichkeiten zur selbsttätigen Abstimmung der Sensorelektronik auf den angeschlossenen Ultraschallwandler bzw. dessen Parameteränderungen werden diskutiert.

Sensorelektronik zur Bestimmung von Reflexionen sensoroberflächennaher Schichten - Vössing, Torsten; Rautenberg, Jens; Henning, Bernd (Fortschritte der Akustik)
In der Ultraschallmesstechnik ist der Einsatz des Impuls-Echoverfahrens verbreitet. Wird nur ein Ultraschallwandler eingesetzt, benötigt man für das sequentielle Senden und Empfangen einen Sende-/Empfangsumschalter. Häufig werden aber nicht nur Impulse gesendet, sondern auch sogenannte Bursts, die aus mehreren Wellenzügen bestehen. Die während des Sendebetriebs empfangenen Ultraschallwellen, die z. B. durch Reflexionen von nahe gelegenen Hindernissen entstehen, können bei diesen umschaltenden Systemen nicht ausgewertet werden. In diesem Beitrag wird eine Sensor-Interface-Elektronik vorgestellt, die das gleichzeitige Senden und Empfangen von Ultraschallsignalen mit nur einem Ultraschallwandler erlaubt. Die dazu erforderliche Trennung von Sende- und Empfangssignal wird durch einen Richtkoppler ermöglicht, der mit vergleichsweise geringem technischem Aufwand aus Breitbandübertragern aufgebaut ist. Eine geeignete Dimensionierung für die verkoppelten Übertrager wurde durch die Analyse der zugehörigen Streumatrix dieses Aufbaus gefunden. Die Arbeitsweise sowie die Bedeutung der Anpassung der Tore des Richtkopplers wird anhand der Ankopplung verschiedener Medien an den Wandler erläutert. Die angekoppelte akustische Last beeinflusst dabei auch die elektrischen Eigenschaften des Sensors. Durch den Einsatz dieser Sensorelektronik wird es möglich, Reflexionen in unmittelbarer Nähe der Sensoroberfläche aufzunehmen, ohne dass z. B. Vorlaufkörper eingesetzt werden müssen. Möglichkeiten zur selbsttätigen Abstimmung der Sensorelektronik auf den angeschlossenen Ultraschallwandler bzw. dessen Parameteränderungen werden diskutiert.

Simultaneous transmitting and receiving with ultrasonic sensors - Vössing, Torsten; Rautenberg, Jens; Kehl, Romina; Henning, Bernd
In many applications ultrasonic transducers are used for transmitting and receiving ultrasonic waves. Ultrasonic sensor systems meet the practical requirements of industrial applications quite well. Typical sensor applications are for example the measurement of distance and thickness. Especially if only one ultrasonic transceiver and the well-known pulse-echo-method are used, the sensor electronics has to switch from transmitting to receiving mode. This is one of the most limiting properties because the probe can not receive echoes from nearby obstacles or thin material layers. This contribution deals with the development of an electronic interface circuit for ultrasonic sensors allowing transmitting and receiving of acoustic signals simultaneously. There are already several methods to separate the transmitted from the received signal for instance the well-known circulator in the telephone, the differential transformer mentioned by Bradfield [1] or a directional coupler [2]. The directional coupler consists of two broadband transformers linked with each other in such a way that it equally distributes the input power at port one to the third and fourth port, while port two is isolated. This circuit is also known as 3 dB directional coupler and makes it possible to get reference echoes directly from the interface between the sensor and the medium of interest. Several reflectors or multiple sound paths such as used in ultrasonic density measurement systems are unnecessary [3].

Ultrasonic measurement of the characteristic acoustic impedance using a directional coupler to analyse reference reflections from thin layers - Vössing, Torsten; Rautenberg, Jens; Schröder, Andreas; Henning, Bernd
In this contribution the application of a directional coupler for analysing reference reflections from thin layers in ultrasonic measurement of the characteristic acoustic impedance is presented. In a prior work ([2]) it was shown, that a directional coupler can be used in combination with an ultrasonic transducer to get reflections from layers that are very close to the transducers surface. Since the directional coupler provides the opportunity to send and receive signals at the same time, these layers can be very thin ({<} 1 mm). Reflections that arrive at the transducer during the sending process can be analysed because the directional coupler separates the receiving signal from the input signal of the transducer. When only one transducer is used to measure the acoustic impedance of a liquid the reflections from the thin layer reach the transducer after a very short time. The reflections sum up and with the concept of reflection and transmission coefficients a relation is found between the measured amplitude and a reference amplitude which was measured before. The exciting signal could be a burst of some periods of a sinusoidal alternating voltage. The advantages of using thin layers for the described task are the small geometry that allows flexible application of the sensor and the minimisation of temperature gradients within the medium because thin layers can follow thermal fluctuations faster than thick ones. In this paper the functional principle and first achievements are presented.

A graduate level course on real-time medical graphics - Domik, Gitta (ACM SIGGRAPH 2007 educators program)

Coregistration and visualization of cardiac CT studies and dynamic PET studies using scene-graphs, direct volume rendering and 2D transfer functions - Fricke, H; Schwier, M; Weise, R; Elsner, A; Fricke, E; Domik, Gitta; Burchert, W (Proc. of the 54th SNM Annual Meeting)

Attitudes towards computer science-computing experiences as a starting point and barrier to computer science - Schulte, Carsten; Knobelsdorf, Maria (ICER)

Lesen im Informatikunterricht - Schulte, Carsten (INFOS)

Das informatische Weltbild von Studierenden - Schulte, Carsten; Knobelsdorf, Maria (INFOS)

Interactive ranking of skylines using machine learning techniques - Cheng, W.; Hüllermeier, Eyke; Seeger, B.; Vladimirskiy, I. (In Proceedings Workshop LWA-2007, Lernen-Wissensentdeckung-Adaptivität, Halle/Saale, Germany)

Evolutionary construction of multiple graph alignments for the structural analysis of biomolecules - Fober, T.; Hüllermeier, Eyke; Mernberger, M. (in Proceedings 17th Workshop Computational Intelligence, Dortmund Germany)

Similarity search over uncertain archaeological data using a modified skyline operator - Vladimirskiy, I.; Hüllermeier, Eyke; Stauch, E. (In Workshop Proceedings from ICCBR-2007 7th International Conference on Case-Based Reasoning, Belfast, Northern Ireland)

On minimizing the position error in label ranking - Hüllermeier, Eyke; Fürnkranz, J. (In Proceedings ECML-2007, 17th European Conference on Machine Learning, Warsawa, Poland, September 2007)

Label ranking in case-based reasoning - Brinker, K.; Hüllermeier, Eyke (In Proceedings ICCBR-2007, 7th International Conference on Case-Based Reasoning, Belfast, Northern Ireland)

Efficient instance-based learning on data streams - Beringer, J.; Hüllermeier, Eyke (In Proceedings ICDM-2007, International Conference on Industrial Data Mining, Leipzig)

Case-based multilabel ranking - Brinker, K.; Hüllermeier, Eyke (in Proceedings IJCAI-07, 20th international Joint Conference on Artificial Intelligence, Hyerabad, India, January 2007)

Taxation of Risky Investment and Paradoxical Investor Behavior - Gries, Thomas; Prior, Ulrich; Sureth-Sloane, Caren

Aufkommenswirkungen des Erbschaftsteuerreformvorschlags der CDU/CSU-Mittelstandsvereinigung - Maiterth, Ralf; Sureth-Sloane, Caren

Die steuerliche Ungleichbehandlung von Anteilen an Kapitalgesellschaften - Müller, Jens (FinanzBetrieb)

Group Simulation and Income Tax Statistics - How Big is the Error? - Müller, Heiko; Sureth-Sloane, Caren

Die Fehlbewertung durch das Stuttgarter Verfahren - eine Sensitivitätsanalyse der Werttreiber von Steuer- und Marktwerten - Müller, Jens

Investitionswirkungen von Übergangsregelungen bei Steuerreformen - Sureth-Sloane, Caren (Festzeitschrift zur Emeritierung von Reinar Lüdeke: Regeln rationaler Finanzpolitik und ihre Anwendung)

Evaluating XPath Queries on XML Data Streams - Böttcher, Stefan; Steinmetz, Rita (Data Management. Data, Data Everywhere, 24th British National Conference on Databases, BNCOD 24)

Data Management for Mobile Ajax Web 2.0 Applications - Böttcher, Stefan; Steinmetz, Rita (Database and Expert Systems Applications, 18th International Conference, DEXA 2007)

XML index compression by DTD subtraction - Böttcher, Stefan; Steinmetz, Rita; Klein, Niklas (ICEIS 2007 - Proceedings of the Ninth International Conference on Enterprise Information Systems)

Fuzzy-relational classificaton : Combining pairwise decomposition techniques with fuzzy preference modeling - Hüllermeier, Eyke; Brinker, K. (in Proceedings EUSFLAT-2007 5th International Conference on the European Society for Fuzzy Logic and Technology, Ostrava, Czech Republic)

Adaptive optimization of the number of clusters in fuzzy clustering, London 2007 - Beringer, J.; Hüllermeier, Eyke (in Proceedings FUZZ-IEEE-07, IEEE International Conference on Fuzzy Systems)

Graph alignment: Fuzzy pattern mining for the structural analysis of protein active sites - Hüllermeier, Eyke; Weskamp, N.; Klebe, G.; Kuhn, D. (in Proceedings FUZZ-IEEE-07, IEEE International Conference on Fuzzy Systems, London)

In defense of fuzzy association analysis - Hüllermeier, Eyke; Yi, Y. (IEEE Transactions on Systems, Man and Cybernetics-Part B: Cybernetics)

Credible case-based inference using similarity profiles - Hüllermeier, Eyke (IEEE Transactions on Knowledge and Data Engineering)

Efficient instance-based learning on data streams - Beringer, J.; Hüllermeier, Eyke (Intelligent Data Analysis)

Comparing probability measures using possibility theory: A notion of relative peakedness - Dubois, D.; Hüllermeier, Eyke (International Journal of Approximate Reasoning)